1999
DOI: 10.1523/jneurosci.19-08-03007.1999
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic and GABAergic Inputs Drive Patterned Spontaneous Motoneuron Activity before Target Contact

Abstract: Patterned spontaneous electrical activity has been demonstrated in a number of developing neural circuits and has been proposed to play a role in refining connectivity once axons reach their targets. Using an isolated spinal cord preparation, we have found that chick lumbosacral motor axons exhibit highly regular bursts of activity from embryonic day 4 (E4) (stage 24-25), shortly after they exit the spinal cord and while still en route toward their target muscles. Similar bursts could be evoked by stimulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
222
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(236 citation statements)
references
References 80 publications
13
222
1
Order By: Relevance
“…4 A and B) revealed that as in control embryos the electroporated embryos exhibited episodes consisting of several bursts every 4 min (Fig. 4 B and C) (25). Thus the electroporation protocol and expression of these constructs over several days did not appear to have any adverse effects on the development of the cord circuits responsible to generating this activity.…”
Section: Activation Of Ro4 and Chr2 Can Be Used To Control Spontaneousmentioning
confidence: 61%
See 2 more Smart Citations
“…4 A and B) revealed that as in control embryos the electroporated embryos exhibited episodes consisting of several bursts every 4 min (Fig. 4 B and C) (25). Thus the electroporation protocol and expression of these constructs over several days did not appear to have any adverse effects on the development of the cord circuits responsible to generating this activity.…”
Section: Activation Of Ro4 and Chr2 Can Be Used To Control Spontaneousmentioning
confidence: 61%
“…4 E and F). Thus light, as has been previously shown for electrical stimulation (24,25), can be used to elicit episodes either by activation of local lumbar interneurons and motoneurons or activation of neurons many cord segments distant.…”
Section: Activation Of Ro4 and Chr2 Can Be Used To Control Spontaneousmentioning
confidence: 80%
See 1 more Smart Citation
“…For example, the neurotransmitter acetylcholine (ACh) is released from embryonic motor neurons (MNs) at the neuromuscular junction (NMJ), and it negatively regulates survival, axon branching, and synapse formation (4)(5)(6)(7). ACh is also released from developing neurons even before they arrive at their target, and it acts in an autocrine and/or paracrine fashion to regulate growth (8), pathfinding (9), spontaneous activity (10), and target selection (11). Whereas the NMJ has served as an excellent model to elucidate the process of synapse formation, the cellular and molecular mechanisms by which ACh regulates this process are still unclear; this is in part because the expression of ACh receptor (AChR) subtypes varies over space and time during the development of this synapse.…”
mentioning
confidence: 99%
“…Although all these motor neurons originate from a common precursor population in ventral neural tube and share many features in common at maturity, each motor pool has unique distinguishing characteristics. Neurons within an individual motor pool reside in a characteristic position in the LMC (Landmesser, 1978), exhibit a distinctive pattern of spontaneous electrical activity (Milner and Landmesser, 1999), express a unique set of LIM homeodomain and ETS transcription factors and cadherins (Tsuchida et al, 1994;Lin et al, 1998;Price et al, 2002), innervate a single target muscle, and receive monosynaptic input from sensory neurons supplying the same muscle (reviewed in Chen et al, 2003). These distinguishing properties of motor pools arise through the sequential activation of different transcriptional networks (reviewed in Shirasaki and Pfaff, 2002).…”
Section: Introductionmentioning
confidence: 99%